Risks of on-pump coronary artery bypass grafting surgery in patients with chronic obstructive pulmonary disease due to sulfur mustard - Firoozabadi, Mehdi Dehghani; Sheikhi, Mohammad Ali; Rahmani, Hossein; Ebadi, Ahmad; Heidari, Amanollah; Gholizadeh, Behnam; Sharifi, Khosrow (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Sulfur mustard (SM) is a toxic chemical agent that belongs to a class of vesicant compounds. In the 1980s it was used by the Iraqi army against Iranian forces. Sulfur mustard severely irritates the skin, eyes and lungs. The highest side effects seen in patients affected by this gas are pulmonary complications including different types of lung diseases such as bronchiolitis. It has also led to a certain type of chronic obstructive pulmonary disease called mustard lung. Similar extra-pulmonary, molecular and hormonal effects can be observed in these patients and patients with chronic obstructive pulmonary disease. Here cardiovascular complications may be one of the most dangerous visible effects. And atherosclerosis is probable following the direct effects or consequential long-term effects of SM. The development of atherosclerosis in these patients is associated with an increased risk of cardiovascular and coronary artery disease. Coronary artery bypass grafting surgery is the treatment of coronary artery disease. Doing this surgery by bypass pump has its own morbidity and due to local and systemic inflammation changes in patients with SM pulmonary disorders it may have more side effects. Therefore, detailed knowledge of inflammatory diseases as well as the serum level or even the local lung fluid of the inflammatory factors in these patients before surgery are needed so that it would be possible to reduce the rate of morbidity and mortality by normalizing the inflammatory conditions of the patients before cardiac surgery.